Relationships between endurance exercise training-induced muscle fiber-type shifting and autophagy in slow- and fast-twitch skeletal muscles of mice - Kwon, Insu; Kim, Kyoung Soo; Lee, Youngil (Physical activity and nutrition, 2024)
[Purpose] Endurance exercise induces muscle fiber-type shifting and autophagy; however, the potential role of autophagy in muscle fiber-type transformation remains unclear. This study examined the relationship between muscle fiber-type shifting and autophagy in the soleus (SOL) and extensor digitorum longus (EDL) muscles, which are metabolically discrete muscles.[Methods] Male C57BL/6J mice were randomly assigned to sedentary control (CON) and exercise (EXE) groups. After 1 week of acclimation to treadmill running, the mice in the EXE group ran at 12-15 m/min, 60 min/day, 5 days/week for 6 weeks. All mice were sacrificed 90 min after the last exercise session, and the targeted tissues were rapidly dissected. The right side of the tissues was used for western blot analysis, whereas the left side was subjected to immunohistochemical analysis.[Results] Endurance exercise resulted in muscle fiber-type shifting (from type IIa to type I) and autophagy (an increase in LC3-II) in the SOL muscle. However, muscle fiber-type transformation and autophagy were not correlated in the SOL and EDL muscles. Interestingly, in contrast to the canonical autophagy signaling pathways, our study showed that exercise-induced autophagy concurs with enhanced anabolic (increased p-AKTSer473/AKT and p-mTOR/mTORSer2448 ratios) and suppressed catabolic (reduced p-AMPKThr172/AMPK ratio) states.[Conclusion] Our findings demonstrate that chronic endurance exercise-induced muscle fiber-type transformation and autophagy occur in a muscle-specific manner (e.g., SOL). More importantly, our study suggests that endurance training-induced SOL muscle fiber-type transition may underlie metabolic modulations caused by the AMPK and AKT/mTOR signaling pathways rather than autophagy.